The social weaving of a reading atmosphere - Sequeiros, Paula (2011)
This paper discusses how public library readers in Almeida Garrett, Porto, create a reading atmosphere, focusing on meanings associated with aural conditions. Through a qualitative, single case study, ethnographic and interview techniques were applied. Readers’ actual practices and discourses, through a theoretical sample, and those of managers, staff and architects were analysed; a spatial analysis was conducted within the framework of social inequalities and power relations. The paper proposes the concept of reading atmosphere and suggests that its social production is based on a tacit, informal code of conduct in which some regular readers played an influential role. Some recommendations on service provision are made.